Influence of physical and psychosocial working conditions for the risk of disability pension among healthy female eldercare workers: Prospective cohort. Issue 4 (June 2020) - Andersen, LL; Villadsen, E; Clausen, T
Aim: To investigate the influence of physical and psychosocial working conditions on the risk of disability pension among eldercare workers. Methods : After responding to a questionnaire in 2005, 4699 healthy female eldercare workers – free from chronic musculoskeletal pain, depressive symptoms and long-term sickness absence – were followed for 11 years in the Danish Register for Evaluation of Marginalization. Time-to-event analyses estimated the hazard ratio (HR) for disability pension from physical exertion during work, emotional demands, influence at work, role conflicts, and quality of leadership. Analyses were mutually adjusted for these work environmental factors as well as for age, education, smoking, leisure physical activity and body mass index. Results : During follow-up, 7.6% received disability pension. Physical exertion and emotional demands were associated with risk of disability pension, and both interacted with age. In age-stratified analyses, older eldercare workers (mean age 53 years at baseline) with moderate and high physical exertion (reference: low) were at increased risk with HRs of 1.51, 95% CI [1.06–2.15] and 2.54, 95% CI [1.34–4.83], respectively. Younger eldercare workers (mean age 36 years at baseline) with moderate emotional demands (reference: low) were at decreased risk with an HR of 0.57, 95% CI [0.37–0.85]. Conclusions : While a higher level of physical exertion is a risk factor for disability pension among older female eldercare workers, a moderate level of emotional demands is associated with lower risk among the younger workers. The age of the worker may be an important factor when providing recommendations for promoting a long and healthy working life.